Be Media Smart: A National Media Literacy Campaign for Ireland - Russell, Philip (Septentrio Conference Series, 2021)
This paper presents Ireland’s public awareness campaign –‘Be Media Smart’-which was launched in Spring 2019 to combat misinformation and fake news and encourage people of all ages to stop, think, and check that information they see, read or hear across any media platform is reliable. Be Media Smart is an initiative of Media Literacy Ireland (MLI), an independent group facilitated by the Broadcasting Authority of Ireland (BAI) to enhance Irish people’s understanding of, and engagement with, media. Group members include large media and social media companies, Government bodies, libraries, academia and voluntary sector organisations. The paper will provide an overview of this national campaign particularly in terms of how a range of organisations includingall library sectors worked together to help empower Irish citizens to make informed media choices about the media content and services that they consume, create, and disseminate across all platforms.Some of the key observations and findings of the Be Media Smart campaign will be presented including the role of libraries and the value of the cross-sector collaborative approach. Challenges, lessons learned and future development plans will also be outlined. ‘Be Media Smart’ provides a best practice exampleof how a unique Irish initiative has helped to advance media and information literacy at national level.